Avaliação da técnica de aplicação de ultrassom fisioterapêutico com bolsa com água - Lima, Lúcio Salustiano de (2018)
Therapeutic ultrasound (TUS) has three forms of application described in the literature, one of them is the one with "water pouch", which method consists of using a rubber glove filled with water as a transmission medium for irregular and / or small surfaces, such as the ankle (irregular) and the metacarpal head (irregular and small, making coupling difficult). After reviewing some databases, it was verified that there are not many articles about this technique, therefore it is not known how much the use of the glove with water influences in the ultrasonic therapy, as well as in obtaining the desired effects in the same. Motivated by this scarcity of scientific data, the technique was studied with two commonly used gloves (latex and nitrile). As there was cavitation, a methodology was developed to avoid it. The results indicate that there is no relevant clinical influence, provided that the methodology described in this study is used.